Scientific Institutions Should Support Inclusive Engagement: Reflections on the AAAS Center for Public Engagement Approach - Kimbrell, Elana; Philippe, Gemima; Longshore, Mary Catherine (Frontiers in Communication, 2022)
Scientists’ engagement with society on critical environmental and health issues is essential to reaching positive and equitable long-term outcomes. We argue that stronger institutional support for public engagement is necessary and that inclusive practices should built into public engagement training and relationships. The American Association for the Advancement of Science (AAAS)’s Center for Public Engagement with Science and Technology provides a model of support for scientists that we believe other scientific institutions can replicate and expand on. This model prioritizes representative and accessible science communication training, resources (e.g., funding and staff and peer support), opportunities to practice engagement, and rewards and incentives for doing engagement. We describe our programs in each of these areas and reflect on how well each builds scientists’ skills and institutional capacity, and whether each embodies and models thoughtful, accessible, and representative engagement. Through these various approaches, the Center communicates to other scientific institutions that engagement by scientists should be valued, celebrated, and supported, and builds capacity for individual scientists to do effective engagement. We argue that these supports can be applied by other scientific institutions to reflect and incorporate society’s diverse needs and concerns, thus truly serving the public and making science and scientific institutions stronger for it.